Immunotherapy and Antivascular Targeted Therapy in Patients’ Treatment with Concurrent Malignant Tumors after Organ Transplantation: Opportunity or Challenge - Bairu Shen; Zi Guo; Peng Huang; Minghua Tan; Xiaoshen Zhang; Siyao Lin; Changshan Song; Jiaqing Wang; Minqian Huang (Journal of Immunology Research)
Objective. To analyze the therapeutic effects and organ rejection of anti-PD-1 immunotherapy or antivascular targeting therapy on patients with combined malignancies after organ transplantation. Methods. We collected retrospective studies on “post-transplantation, cancer, immunotherapy, and vascular targeting therapy” in Embase, Wanfang database, Cochrane Library, VIP databases, CNKI, and PubMed, and the case data were organized and analyzed. Results. Data from only 40 papers met our requirements, which included 2 literature reviews, 4 original researches, and 34 case reports from 2016 to 2020. A total of 40 studies involving 66 patients were included, who were divided into 3 groups (patients using CTLA-4 inhibitors, group 1; patients who received sequential or concurrent anti-PD-1 and anti-CTLA-4 therapy, group 2; and patients using PD-1/PD-L1 inhibitors, group 3). There was no statistical difference in patients’ DCR between the three groups (P>0.05). Also, compared with group 2, there was no statistically significant difference in recipient organ rejection in group 1 and group 3 (P>0.05). The DCR rate for antivascular targeted therapy is approximately 60%. Conclusions. Immunotherapy should be carefully selected for patients with combined malignancies after organ transplantation. Antivascular targeted therapy is one of the options worth considering; the risk of side effects of drug therapy is something that needs to be closely monitored when combined with immunotherapy.